2013
DOI: 10.1021/mp300606p
|View full text |Cite
|
Sign up to set email alerts
|

A New Way of Stabilization of Furosemide upon Cryogenic Grinding by Using Acylated Saccharides Matrices. The Role of Hydrogen Bonds in Decomposition Mechanism

Abstract: Recently it was reported that upon mechanical milling of pure furosemide significant chemical degradation occurs (Adrjanowicz et al. Pharm. Res.2011, 28, 3220-3236). In this paper, we present a novel way of chemical stabilization amorphous furosemide against decomposing that occur during mechanical treatment by preparing binary mixtures with acylated saccharides. To get some insight into the mechanism of chemical degradation of furosemide induced by cryomilling, experimental investigations supported by density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…It has been correlated with a higher crystallization barrier for crystallization binary solid dispersion of NIF with acetated disaccharides and, consequently, with better stabilization of the drug in such binary systems both above and below the glass transition temperature. Acetylated sugars like maltose, sucrose, and glucose have also been used to increase the chemical stability of furosemide, 34 which easily degraded as a neat drug upon melting or cryogenic grinding. Theoretical computations have indicated that H-bonds play an important role in the destabilization mechanism of furosemide upon milling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been correlated with a higher crystallization barrier for crystallization binary solid dispersion of NIF with acetated disaccharides and, consequently, with better stabilization of the drug in such binary systems both above and below the glass transition temperature. Acetylated sugars like maltose, sucrose, and glucose have also been used to increase the chemical stability of furosemide, 34 which easily degraded as a neat drug upon melting or cryogenic grinding. Theoretical computations have indicated that H-bonds play an important role in the destabilization mechanism of furosemide upon milling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, furosemide cryomilled with acylated glucose, acylated maltose, and acylated sucrose is much more soluble with respect to the crystalline form of this active pharmaceutical ingredient (API). 34 …”
Section: Introductionmentioning
confidence: 99%
“…Recent reports show that they can be used as energy supply in batteries or to stabilize the native structure of proteins or labile Active Pharmaceutical Ingredients. [1][2][3][4][5] Carbohydrates also play a key role in many vital biophysical processes. 6 These materials appear in a dynamic equilibrium of different isomeric states: i.e., in different cyclic or an open chain conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the preparation of the APIs in the amorphous form is well known although challenging (4)(5)(6)(7)(8)(9)(10). Amorphous substances show altered physico-chemical properties in comparison to their crystalline counterparts (9).…”
Section: Introductionmentioning
confidence: 99%
“…Acetylated starch is classified by the Food and Drug Administration (FDA) as a Generally Recognized as Safe (GRAS) material. Numerous investigations regarding the use of various sugar derivatives, i.e., acetylated sucrose, glucose, maltose, galactose, to stabilize amorphous forms of drugs, such as indomethacin, itraconazole, and nifedipine have been published (6,17,18). Solid dispersions composed of amorphous APIs have been obtained by melting with appropriate ratios of active substances and modified saccharides followed by rapid cooling.…”
Section: Introductionmentioning
confidence: 99%